Comprehensive Literature Review on Metal Nanoparticle for Enhanced Shelf Life of Mango Fruit - Yalew Yiblet; Indiris Abdu; Basaznew Belew (The Scientific World Journal)
The purpose of this review was to investigate the application of metal nanoparticles in fruit shelf life extension. Despite growing interest in nanoparticles and their potential applications, there are currently few effective methods for prolonging the shelf life of fruits. The study concentrated on the principles underlying the shelf life extension of metallic nanoparticles, including copper oxide, zinc oxide, silver, and titanium oxide. The biological properties of nanoparticles, especially those with antibacterial qualities, have drawn interest as possible fruit preservation solutions. Many conventional preservation methods have drawbacks, including expensive production costs, short shelf lives, undesirable residues, and the incapacity to properly keep perishable fruits in their natural environments. Techniques for extending shelf life based on nanotechnology have the potential to get around these problems. The review focused on the effective use of environmentally benign, green synthesis-produced nanoparticles to extend the fruit shelf life. The ability of these nanoparticles to successfully preserve fresh fruits was established. The results imply that fruit preservation by the use of nanoparticle synthesis techniques may be a viable strategy, offering a more effective and sustainable substitute for traditional procedures.